Progress in Scale Modeling Summary of the First International Symposium on Scale Modeling (ISSM I in 1988) and Selected Papers from Subsequent Symposia (ISSM II in 1997 through ISSM V in 2006) - Saito, Kozo (Springer Netherlands : Imprint: Springer, 2008)
This book is a selection of seminal papers given at the past International Symposia on Scale Modeling (ISSM). The International Scale Modeling Committee consisting of active worldwide researchers in scale modeling celebrates its twentieth anniversary in 2008. The Committee is interdisciplinary, attracting researchers from a broad range of scientific and engineering disciplines. Scale modeling is a simplifying and clarifying tool used by scientists and engineers in many disciplines to help them grasp essential or salient aspects of bewilderingly complex systems, mechanisms and phenomena -- to see the forest when there are many trees. Scale modeling techniques are also used when it would be too expensive or too difficult to test the system of interest. In addition, scale modeling is an approach that offers engineers and designers a new point of view, liberating creative and innovative ideas and solutions. Scale modeling is employed to study weather systems, diffusion of pollution in air or water, chemical process in 3-D turbulent flow, multiphase combustion, flame propagation, biological systems, behavior of materials at nano- and micro- scales and so on. Scale modeling would be even more widely used if more new material was readily available. The objective in publishing these papers in one place is to remedy the lack of available material on scale modeling and to make a book that will be useful in university courses (both graduate and undergraduate), and in industry short courses.